Pengaruh Ekstrak Daun Pepaya (Carica papaya L.) dengan Berbagai Jenis Pelarut terhadap Pertumbuhan Escherichia coli (Literature Review) - Raudah, Siti; Mawardani, Maya Tamara; Amelia, Ria (Institut Teknologi Kesehatan dan Sains Wiyata Husada Samarinda, 2024)
Background: Papaya leaf (Carica papaya L.) can be used as an antimicrobial. Phytochemical analysis proves papaya leaves contain antimicrobial compounds, including flavonoids, tannins, alkaloids, steroids, and saponins. In this study, the bacteria used were Escherichia coli, and the extraction process used several types of solvents, namely ethanol, methanol, water, and ethyl acetate. Purpose: This study aimed to determine the growth of Escherichia coli. Method: Literature review. The search started from January 13, 2021, to June 15, 2021, through electronic-based searches, including the Garuda Portal, Google Scholar, Research Gate, and Science Direct. Result: The obtained results were that all types of solvents have inhibition zones on the growth of Escherichia coli, where solvents of ethanol, methanol, water, and ethyl acetate had the highest inhibition zone respectively, namely 18,6 mm, 20 mm, 12 mm, and 12 mm. Conclusion: Papaya leaf extract using various types of solvents has effectiveness in inhibiting the growth of Escherichia coli